2011 IEEE International Ultrasonics Symposium 2011
DOI: 10.1109/ultsym.2011.0568
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of langasite for application in high temperature SAW sensors

Abstract: Experimental SAW resonator structures with iridium electrodes were fabricated on Y-cut of langasite with few different propagation directions and their characteristics were measured in a wide temperature interval, up to 700ºC, and compared with simulations. Between two sets of material constants reported by Bungo one set was selected as providing much better agreement with experiments, for the analyzed orientations. Further improvement of simulation accuracy was achieved via after-correction of the calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
(16 reference statements)
1
5
1
Order By: Relevance
“…15). The results are consistent with data from Sakharov et al [17]. At higher temperatures (580°C and above), the signals of the latter cuts decrease slightly but signal analysis is still possible (Fig.…”
Section: Measurement Results and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…15). The results are consistent with data from Sakharov et al [17]. At higher temperatures (580°C and above), the signals of the latter cuts decrease slightly but signal analysis is still possible (Fig.…”
Section: Measurement Results and Discussionsupporting
confidence: 92%
“…14). Small discrepancies between these results and the data coming from Sakharov et al [17] can be observed. Their origin can be likely attributed to the difference At higher temperatures (580°C and above), the signals of the latter cuts decrease slightly but signal analysis is still possible (Fig.…”
Section: Measurement Results and Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…However, their results were based on a numerical technique and were not compared with experimental results, so we are unable to verify the appropriateness of the analysis. Lots of experimental investigations on LGS SAW devices with Euler angles such as (0 , 138.5 , ), (0 , 90 , ) and (0 , 22 , ) have been conducted [ 12 , 22 , 23 , 24 ], however only one mode was investigated in these works. For example [ 12 ] studied the high temperature parameters of Pt LGS SAW devices with an Euler angle (0 , 138.5 , 26 ), which only referred to Rayleigh waves.…”
Section: Introductionmentioning
confidence: 99%